Cas1 and Fen1 Display Equivalent Functions During Archaeal DNA Repair - Wörtz, Julia; Smith, Victoria; Fallmann, Jörg; König, Sabine; Thuraisingam, Tharani; Walther, Paul; Urlaub, Henning; Stadler, Peter F.; Allers, Thorsten; Hille, Frank; Marchfelder, Anita (Frontiers in Microbiology, 2022)
CRISPR-Cas constitutes an adaptive prokaryotic defence system against invasive nucleic acids like viruses and plasmids. Beyond their role in immunity, CRISPR-Cas systems have been shown to closely interact with components of cellular DNA repair pathways, either by regulating their expression or via direct protein-protein contact and enzymatic activity. The integrase Cas1 is usually involved in the adaptation phase of CRISPR-Cas immunity but an additional role in cellular DNA repair pathways has been proposed previously. Here, we analysed the capacity of an archaeal Cas1 from Haloferax volcanii to act upon DNA damage induced by oxidative stress and found that a deletion of the cas1 gene led to reduced survival rates following stress induction. In addition, our results indicate that Cas1 is directly involved in DNA repair as the enzymatically active site of the protein is crucial for growth under oxidative conditions. Based on biochemical assays, we propose a mechanism by which Cas1 plays a similar function to DNA repair protein Fen1 by cleaving branched intermediate structures. The present study broadens our understanding of the functional link between CRISPR-Cas immunity and DNA repair by demonstrating that Cas1 and Fen1 display equivalent roles during archaeal DNA damage repair.